DAMPAK FINANCIAL TECHNOLOGY TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA PERIODE 2019-2022 - Regita Amalia Ramadhani; Al Muizzuddin Fazaalloh (Contemporary Studies in Economic, Finance and Banking, 2024)
This study examines the impact of fintech on income inequality using macroeconomic indicators in 34 Indonesian provinces in 2019 - 2022. The independent variables used are fintech, economic growth, and inflation while the dependent variable is income inequality. This study uses a quantitative approach in the form of annual fintech lending statistical reports from 2019 to 2022. Secondary data sourced from OJK and BPS is then analyzed using panel data regression. It is concluded that fintech have a positive influence on income inequality. Economic growth has no effect on income inequality. While inflation has a negative effect on income inequality.